Half bad - Green, Sally (Novelist) (New York, New York : Viking, an imprint of Penguin Group (USA), 2014)
In modern-day England, where witches live alongside humans, Nathan, son of a White witch and the most powerful Black witch, must escape captivity before his seventeenth birthday and receive the gifts that will determine his future.
Keywords: Witches -- Fiction; Good and evil -- Fiction; Family life -- England -- Fiction; Toleration -- Fiction; Fathers and sons -- Fiction; Prisoners -- Fiction; JUVENILE FICTION / Fantasy & Magic; JUVENILE FICTION / Boys & Men; JUVENILE FICTION / Family / General (see also headings under Social Issues).; JUVENILE FICTION / Social Issues / General (see also headings under Family).; England -- Fiction